Occlusion of M1 segment after superficial temporal artery-middle cerebral artery bypass in a giant M1 aneurysm with Onyx-34 injected via a double-lumen balloon under balloon inflation. (31st May 2013) - Clarençon, Frédéric; Nouet, Aurelien; Redondo, Aimée; Di Maria, Federico; Iosif, Christina; Le Jean, Lise; Chiras, Jacques; Sourour, Nader
Abstract : A 29-year-old patient attended our institution for recurrent strokes related to a giant partially thrombosed M1 aneurysm. Superficial temporal artery-middle cerebral artery (STA-MCA) bypass and subsequent occlusion of both the aneurysm and the dysplastic M1 segment were planned. However, owing to the shortness of the non-dysplastic segment of M1 and the risk of occlusion of the lenticulostriate arteries, the use of a double-lumen balloon was considered for coiling and subsequent injection of Onyx. STA-MCA bypass was performed using a regular technique. Endovascular occlusion of both the aneurysm and the parent artery was subsequently performed by means of coils and Onyx-34 that was injected via the Ascent balloon under balloon inflation. No complications were recorded and no stroke was observed on control MRI. The injection of Onyx-34 through a double-lumen balloon under balloon inflation is a quick and safe technique for precise occlusion of a parent artery.